Microtubule Actin Cross-Linking Factor (Macf): A Hybrid of Dystonin and Dystrophin That Can Interact with the Actin and Microtubule Cytoskeletons - Leung, Conrad L. (The Rockefeller University Press, 1999)
We cloned and characterized a full-length cDNA of mouse actin cross-linking family 7 (mACF7) by sequential rapid amplification of cDNA ends–PCR. The completed mACF7 cDNA is 17 kb and codes for a 608-kD protein. The closest relative of mACF7 is the Drosophila protein Kakapo, which shares similar architecture with mACF7. mACF7 contains a putative actin-binding domain and a plakin-like domain that are highly homologous to dystonin (BPAG1-n) at its NH(2) terminus. However, unlike dystonin, mACF7 does not contain a coiled–coil rod domain; instead, the rod domain of mACF7 is made up of 23 dystrophin-like spectrin repeats. At its COOH terminus, mACF7 contains two putative EF-hand calcium-binding motifs and a segment homologous to the growth arrest–specific protein, Gas2. In this paper, we demonstrate that the NH(2)-terminal actin-binding domain of mACF7 is functional both in vivo and in vitro. More importantly, we found that the COOH-terminal domain of mACF7 interacts with and stabilizes microtubules. In transfected cells full-length mACF7 can associate not only with actin but also with microtubules. Hence, we suggest a modified name: MACF (microtubule actin cross-linking factor). The properties of MACF are consistent with the observation that mutations in kakapo cause disorganization of microtubules in epidermal muscle attachment cells and some sensory neurons.